Left-right asymmetric expression of the Nodal-Lefty-Pitx2 module in developing turtle forebrain - Kajikawa, Eriko; Miki, Toru; Takeda, Masayoshi; Kiyonari, Hiroshi; Hamada, Hiroshi (Frontiers in Cell and Developmental Biology, 2022)
The epithalamus of zebrafish shows morphological and molecular left-right (L-R) asymmetry, but such asymmetry is not apparent in tetrapods. To provide further insight into the evolutionary diversity of brain L-R asymmetry, we have now examined the developing brains of reptile embryos for expression of Nodal, Lefty, and Pitx2. Two turtle species, the Chinese softshell turtle and the red-eared slider turtle, showed left-sided expression of these three genes in the developing forebrain, with this expression occurring after Nodal expression at the lateral plate and the L-R organizer has disappeared. Nodal activity, as revealed by the detection of phosphorylated Smad2/3, was also apparent in the neural epithelium on the left side in both turtle species. In the Chinese softshell turtle, the habenula did not show apparent asymmetry in size and the parapineal organ was absent, but the expression of Kctd12 in the habenula showed a small yet reproducible asymmetry. In contrast to the turtles, L-R asymmetric expression of Nodal, Lefty, Pitx2, or Kctd12 was not detected in the developing brain of the Madagascar ground gecko. The transcriptional enhancer (ASE) responsible for the asymmetric expression of Nodal, Lefty, and Pitx2 was conserved among reptiles, including the Chinese softshell turtle and Madagascar ground gecko. Our findings suggest that Nodal, Lefty, and Pitx2 have the potential to be asymmetrically expressed in the developing brain of vertebrates, but that their expression varies even among reptiles.